Therapeutic Potential of Piperine: A Comprehensive Review - Singh, Sonia; Shukla, Arpit (Natural Products Journal, The, 2024)
Piperine, an alkaloid from black pepper, has demonstrated diverse pharmacological properties and potential therapeutic applications. Piperine content varies with the pepper plant and ranges from 2 to 7.4% in black pepper. Piperine possesses remarkable biological properties, including antioxidant, anti-inflammatory, antibacterial, anticancer, neuroprotective, and hepatoprotective qualities. Its ability to affect numerous signaling pathways and biological targets implicated in disease development is responsible for these functions. Studies have shown piperine to have high antioxidant activity, which aids in reducing oxidative stress and preventing cellular damage. It has been established that its anti-inflammatory effects suppress the generation of pro-inflammatory mediators, thereby relieving inflammation-related diseases. This review emphasizes and examines piperine's medical and health-promoting benefits and proposed mechanisms of action in health promotion and illness prevention.
Keywords: absorption